Polycomb Requires Chaperonin Containing TCP-1 Subunit 7 for Maintaining Gene Silencing in Drosophila - Shaheen, Najma; Akhtar, Jawad; Umer, Zain; Khan, Muhammad Haider Farooq; Bakhtiari, Mahnoor Hussain; Saleem, Murtaza; Faisal, Amir; Tariq, Muhammad (Frontiers in Cell and Developmental Biology, 2021)
In metazoans, heritable states of cell type specific gene expression patterns linked with specialization of various cell types constitute transcriptional cellular memory. Evolutionarily conserved Polycomb group (PcG) and trithorax group (trxG) proteins contribute to the transcriptional cellular memory by maintaining heritable patterns of repressed and active expression states, respectively. Although chromatin structure and modifications appear to play a fundamental role in maintenance of repression by PcG, the precise targeting mechanism and the specificity factors that bind PcG complexes to defined regions in chromosomes remain elusive. Here we report a serendipitous discovery that uncovers an interplay between Polycomb (Pc) and CCT7 subunit of TCP-1 Ring Complex (TRiC) chaperonin in Drosophila. CCT7 interacts with Pc at chromatin to maintain repressed states of homeotic and non-homeotic targets of PcG, which supports a strong genetic interaction observed between Pc and CCT7 mutants. Depletion of CCT7 results in dissociation of Pc from chromatin and redistribution of an abundant amount of Pc in cytoplasm. We propose that CCT7 is an important modulator of Pc, which helps Pc recruitment at chromatin and compromising CCT7 can directly influence an evolutionary conserved epigenetic network that supervises the appropriate cellular identities during development and homoeostasis of an organism.